THE IMPACTS OF INDIGENOUS-CHINESE RELATIONS ON MUSLIM-CHRISTIAN RELATIONS: ECONOMIC, POLITICAL, SOCIAL, CULTURAL, AND HISTORICAL ANALYSIS - Bambang Sudibyo (Faculty of Economics and Business, Universitas Gadjah Mada, 1997)
Tensions between the Muslims and the Christians have been high in the 90s. The tensions, this writer believes, are strongly confounded by ethnic prijudice beween the predominantly Muslim poor indigeneous and predominantly Christian wealthy Chinese. Relaxing the just mentioned tensions, therefore, should precede any other attemls to relax the tensions between the Muslims and the Christians. This writer proposes Malaysian model of affirmative programs for the Indegeneous to relax tension between the Indegeneous and the Christians, and therefore the Muslims and the. Christians